Survey of Aquatic macroinvertebrates Stream Lagoa Serena, Institute of Biotechnology, Uniara: the Possible Impact Assessment - Pinto, Alessandra dos Santos (2010)
The construction of reservoirs in streams or rivers has altered the aquatic ecosystems. One of these impacts is the change from lotic to lentic systems, influencing the structure and the functioning of this environment and, consequently, modifying the aquatic fauna. Aquatic macroinvertebrates are the most commonly biological indicators in the assessment of aquatic ecosystems, because they reflect the environmental changes and participate in nutrient cycling and energy flow. The aim of this study was to analyze the macroinvertebrates community of a stream located in the Institute of Biotechnology (Ibiotec-Uniara) and to evaluate the possible environmental impact of damming. Two samples were collected from two different sites, downstream and upward the dam where the macroinvertebrates were collected, using a "D" aquatic net, by the sweeping method, and were identified using specific literature. A total of 289 organisms were identified belonging to 15 taxons of macroinvertebrates. The diversity index (Shannon), species richness (Margalef), and dominance index were calculated. In site 1, we found a low species diversity, but with a high abundance of organisms, with the dominance of the Chironomidae family. In site 2, we found more diversity, but low abundance, with the predominance of the Oligochaeta. Apparently, the impoundment has not influenced the diversity of the aquatic fauna, however, the low diversity of riparian vegetation observed in the sites and the presence of the sugar-cane culture in the adjacent areas could be influencing the richness and the diversity of the organisms.